2008
DOI: 10.3945/jn.108.094144
|View full text |Cite
|
Sign up to set email alerts
|

Type I Diabetes Leads to Tissue-Specific DNA Hypomethylation in Male Rats

Abstract: Numerous perturbations of methyl group and homocysteine metabolism have been documented as an outcome of diabetes. It has also been observed that there is a transition from hypo- to hyperhomocysteinemia in diabetes, often concurrent with the development of nephropathy. The objective of this study was to characterize the temporal changes in methyl group and homocysteine metabolism in the liver and kidney and to determine the impact these alterations have on DNA methylation in type 1 diabetic rats. Male Sprague-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
58
3
4

Year Published

2011
2011
2013
2013

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 76 publications
(72 citation statements)
references
References 52 publications
(88 reference statements)
7
58
3
4
Order By: Relevance
“…The hyperglycemic state did not show any significant difference in methylation pattern of germ cells after one or two spermatogenesis cycle except in preleptotene/zygotene cell population where labeling index was higher than control at 72 days suggesting hypermethyation. Diabetes induced perturbations of methylation has been observed in tissue-specific fashion [6] although the germ cell methylation changes are not reported till date. The changes in methylation pattern is a particularly a novel observation and supports our hypothesis that hyperglycemic condition affects germ cell methylation and may have implications on reproductive outcome.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The hyperglycemic state did not show any significant difference in methylation pattern of germ cells after one or two spermatogenesis cycle except in preleptotene/zygotene cell population where labeling index was higher than control at 72 days suggesting hypermethyation. Diabetes induced perturbations of methylation has been observed in tissue-specific fashion [6] although the germ cell methylation changes are not reported till date. The changes in methylation pattern is a particularly a novel observation and supports our hypothesis that hyperglycemic condition affects germ cell methylation and may have implications on reproductive outcome.…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation is catalyzed by DNA methyl transferases (DNMTs) which regulate gene expression during development. It has been shown that diabetes-induced perturbation of methyl group lead to functional hypomethylation of DNA in a tissue specific fashion [6].…”
Section: Introductionmentioning
confidence: 99%
“…This shift is also reflected in other 270 gluconeogenic states, such as diabetes. We and others have demonstrated that a diabetic state or 271 administration of synthetic glucocorticoid compounds has a major impact on methyl group and 272 homocysteine metabolism [23][24][25][26][49][50][51][52]. A consistent finding from these reports is a reduction 273 in circulating homocysteine concentrations owing to an increase in folate-independent 274 remethylation (i.e., BHMT) and catabolism of homocysteine through the transsulfuration 275 pathway.…”
mentioning
confidence: 88%
“…This was based on our previous 95 research demonstrating that a gluconeogenic state and related hormonal alterations, similar to 96 what is exhibited as a function of exercise, results in reduced homocysteine concentrations via 97 enhanced folate-independent remethylation of homocysteine, as well as increased catabolism 98 [23][24][25][26] initially housed in groups of 2 or 3 in a 12-h light: dark cycle and provided an AIN-93G semi-120 purified diet (Table 1) and water ad libitum [28]. No antibiotics were added to the diets or 121 drinking water, resulting in a moderate degree of folate deficiency as we have previously 122…”
mentioning
confidence: 99%
See 1 more Smart Citation